2007
DOI: 10.1097/mca.0b013e3282a30665
|View full text |Cite
|
Sign up to set email alerts
|

Increased platelet activity in patients with isolated coronary artery ectasia

Abstract: In conclusion, we have shown for the first time that patients with isolated CAE have raised levels of plasma P-selectin, beta-TG and PF4 compared with control participants with angiographically normal coronary arteries, suggesting increased platelet activation in patients with CAE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 27 publications
1
30
0
2
Order By: Relevance
“…This is very intriguing because the destruction of the musculoelastic component of the vascular media is assumed to be irreversible. Single-antiplatelet therapy may be warranted for primary prevention of cardiovascular events in isolated CAE [52,65,69,70]. Addition of lifetime systemic anticoagulation therapy may be recommended for secondary, but not primary prevention [2,52,65,71].…”
Section: Managementmentioning
confidence: 99%
“…This is very intriguing because the destruction of the musculoelastic component of the vascular media is assumed to be irreversible. Single-antiplatelet therapy may be warranted for primary prevention of cardiovascular events in isolated CAE [52,65,69,70]. Addition of lifetime systemic anticoagulation therapy may be recommended for secondary, but not primary prevention [2,52,65,71].…”
Section: Managementmentioning
confidence: 99%
“…The changes in blood viscosity, platelet activation, activation of coagulation system and the altered flow properties of blood in ectasic segments may cause thrombosis within this segment, consequently, which may be responsible for myocardial ischemia/infarction in patients with CAE. Yasar et al [21] showed that patients with CAE have raised levels of plasma P-selectin, beta-thromboglobulin (b-TG) and PF4 compared with control group, suggesting increased platelet activation in patients with CAE.…”
Section: Discussionmentioning
confidence: 98%
“…13 Additionally, CAE patients exhibited increased platelet activation, with higher levels of plasma P-selectin, b-thromboglobulin and platelet factor 4, in comparison with NCA subjects. 23 C. pneumoniae IgG levels were the only marker of infection, among those that were studied, that were significantly higher in CAE patients than in NCA subjects. C. pneumoniae IgG tests were positive in 98.9% of CAD and 98.5% of CAE patients, compared to 83.5% in NCA subjects.…”
Section: Activation Markers In Peripheral Bloodmentioning
confidence: 99%
“…The search yielded 22 potentially relevant nonrandomized and retrospective studies published from 2000 to 2013. [6][7][8][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Exclusion criteria described in the articles selected included the following: recent or current myocardial infarction, acute coronary syndromes, left ventricular dysfunction, left ventricular hypertrophy, cardiomyopathies, congenital heart disease, valvular heart disease, inflammatory arrhythmias or immunologic diseases, active infection, hepatic, renal or thyroid functional abnormalities, immunosuppressive therapy and statin use.…”
Section: Methodsmentioning
confidence: 99%